Analytical model of LDMOS with a double step buried oxide layer. (September 2016) - Yuan, Song; Duan, Baoxing; Cao, Zhen; Guo, Haijun; Yang, Yintang
Highlights: The analytic model for the BODS (Buried Oxide Double Step Silicon On Insulator) structure is achieved. The breakdown voltage enhancement of the BODS with about 30% higher than conventional SOI LDMOS is observed in both analytical and simulation results. The electric field modulation effect is explained through the analytical model. The fully depletion criterion and the RESURF criterion for the BODS structure is achieved. The different breakdown conditions at the junctions in the device are analyzed. Abstract: In this paper, a two-dimensional analytical model is established for the Buried Oxide Double Step Silicon On Insulator structure proposed by the authors. Based on the two-dimensional Poisson equation, the analytic expressions of the surface electric field and potential distributions for the device are achieved. In the BODS (Buried Oxide Double Step Silicon On Insulator) structure, the buried oxide layer thickness changes stepwise along the drift region, and the positive charge in the drift region can be accumulated at the corner of the step. These accumulated charge function as the space charge in the depleted drift region. At the same time, the electric field in the oxide layer also varies with the different drift region thickness. These variations especially the accumulated charge will modulate the surface electric field distribution through the electric field modulation effects, which makes the surface electric field distribution more uniform. As a result, the breakdown voltage of the device is improved by 30% compared with the conventional SOI structure. To verify the accuracy of the analytical model, the device simulation software ISE TCAD is utilized, the analytical values are in good agreement with the simulation results by the simulation software. That means the established two-dimensional analytical model for BODS structure is valid, and it also illustrates the breakdown voltage enhancement by the electric field modulation effect sufficiently. The established analytical models will provide the physical and mathematical basis for further analysis of the new power devices with the patterned buried oxide layer.